European Commission international data and information exchange systems to assist EU Member States in case of radiological and nuclear emergencies. (2nd July 2007) - De Cort, Marc; De Vries, Gerhard; Galmarini, Stefano
Shortly after the Chernobyl nuclear power plant accident the European Commission (EC) initiated various activities in order to make early notification and reliable radiological information available to the European Union (EU) Member States in case of nuclear accidents. The Radioactivity Environmental Monitoring (REM) group at the Institute for Environment and Sustainability (IES) of the Joint Research Centre (JRC) in Ispra, Italy, is responsible for the scientific and technical development of three closely related projects that should be a valuable source of information for decision support in Europe during major radiological accidents, i.e.: the European Community Urgent Radiological Information Exchange (ECURIE), the EUropean Radiological Data Exchange Platform (EURDEP) and ENSEMBLE. Starting from the legal background, we describe these information systems in detail with an emphasis on the current status, the gained experience and the planned future developments.